Clinical Implications of 20-Hydroxyeicosatetraenoic Acid in the Kidney, Liver, Lung and Brain: An Emerging Therapeutic Target - Osama H. Elshenawy; Sherif M. Shoieb; Anwar Mohamed; Ayman O.S. El-Kadi (MDPI AG, 2017)
Cytochrome P450-mediated metabolism of arachidonic acid (AA) is an important pathway for the formation of eicosanoids. The ω-hydroxylation of AA generates significant levels of 20-hydroxyeicosatetraenoic acid (20-HETE) in various tissues. In the current review, we discussed the role of 20-HETE in the kidney, liver, lung, and brain during physiological and pathophysiological states. Moreover, we discussed the role of 20-HETE in tumor formation, metabolic syndrome and diabetes. In the kidney, 20-HETE is involved in modulation of preglomerular vascular tone and tubular ion transport. Furthermore, 20-HETE is involved in renal 19 ischemia/reperfusion (I/R) injury and polycystic kidney diseases. The role of 20-HETE in the liver is not clearly understood although it represents 50%-75% of liver CYP-dependent AA metabolism, and it is associated with liver cirrhotic ascites. In the respiratory system, 20-HETE plays a role in pulmonary cell survival, pulmonary vascular tone and tone of the airways. As for the brain, 20-HETE is involved in cerebral I/R injury. Moreover, 20-HETE has angiogenic and mitogenic properties and thus helps in tumor promotion. Several inhibitors and inducers of the synthesis of 20-HETE as well as 20-HETE analogues and antagonists are recently available and could be promising therapeutic options for the treatment of many disease states in the future.